Comprehensive study of the phenolic composition of the edible parts of jambolan fruit (Syzygium cumini (L.) Skeels) - Carvalho Tavares, Iasnaia Maria de [UNESP]; Lago-Vanzela, Ellen Silva [UNESP]; Gomes Rebello, Ligia Portugal; Ramos, Afonso Mota; Gomez-Alonso, Sergio; Garcia-Romero, Esteban; Da-Silva, Roberto [UNESP]; Hermosin-Gutierrez, Isidro (Elsevier B.V., 2016)
Jambolan fruit has been used in traditional Indian medicine and has recently attracted interest as a functional food. The comprehensive study by HPLC-DAD-ESI-MS/MS has revealed the occurrence of around 74 individual phenolic compounds in the edible parts of jambolan, including 9 anthocyanins (mainly based on delphinidin, petunidin and malvidin), 9 flavonols (myricetin, laricitrin and syringetin glycosides), 19 flavanonols (dihexosides of dihydromyricetin and its methylated derivatives), 8 flavan-3-ol monomers (mainly gallocatechin), 13 gallotanins and 13 ellagitanins, together with some proanthocyanidins (highly galloylated prodelphinidins) and free gallic and ellagic acids. No hydroxycinnamic acid derivatives were detected. The skin of the jambolan fruit accumulated great amounts of phenolic compounds, almost all of the non-tannin phenolics. In contrast, condensed tannins (proanthocyanidins) and hydrolyzable tannins (gallotannins and ellagitannins) were present in both edible parts, accounting for greater amounts in the skin. Overall, the main phenolics of jambolan were anthocyanins and hydrolyzable tannins (similar amounts of gallotannins and ellagitanins), followed by flavanonols, flavonols and flavan-3-ols. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Jambolan; Anthocyanins; Flavonols; Flavanonols; Flavan-3-ols; Proanthocyanidins; Hydrolyzable tannins